Influence of Na+-Independent Cl¯-HCO3¯ Exchange on the Slow Force Response to Myocardial Stretch - Cingolani, Horacio Eugenio (2003)
Previous work demonstrated that the slow force response (SFR) to stretch is due to the increase in calcium transients (Ca2+T) produced by an autocrine-paracrine mechanism of locally produced angiotensin II/endothelin activating Na+-H+ exchange. Although a rise in pHi is presumed to follow stretch, it was observed only in the absence of extracellular bicarbonate, suggesting pHi compensation through the Na+-independent Cl¯-HCO3¯ exchange (AE) mechanism. Because available AE inhibitors do not distinguish between different bicarbonate-dependent mechanisms or even between AE isoforms, we developed a functional inhibitory antibody against both the AE3c and AE3fl isoforms (anti-AE3Loop III) that was used to explore if pHi would rise in stretched cat papillary muscles superfused with bicarbonate after AE3 inhibition. In addition, the influence of this potential increase in pHi on the SFR was analyzed. In this study, we present evidence that cancellation of AE3 isoforms activity (either by superfusion with bicarbonate-free buffer or with anti-AE3Loop III) results in pHi increase after stretch and the magnitude of the SFR was larger than when AE was operative, despite of similar increases in [Na+]i and Ca2+T under both conditions. Inhibition of reverse mode Na+-Ca2+ exchange reduced the SFR to the half when the AE was inactive and totally suppressed it when AE3 was active. The difference in the SFR magnitude and response to inhibition of reverse mode Na+-Ca2+ exchange can be ascribed to a pHi-induced increase in myofilament Ca2+ responsiveness.